Globally updated mesochronous design style. - Soderquist, I. (IEEE Journal of solid state circuits)
In large-scale and high-speed digital systems, global synchronization has frequently been used to protect clocked I/O from data failure due to metastability. Synchronous design styles are widely used, easy to grasp and to implement, and also well supported by logic synthesis tools. There are many drawbacks with global synchronization. Most important is the relationship between physical size and maximum clock frequency, which will approach its limit as clock frequency and system size increase simultaneously. The purpose of this proposed Globally Updated Mesochronous (GUM) design style is to overcome those drawbacks by identifying all global signal links in the system and adding synchronization circuits to these. System level simplicity, inherited from synchronous design and its tool support, is retained. In this paper, the GUM design style is described, analyzed, and demonstrated. Experimental results from a large-scale high-speed system using three 0.8-μm BiCMOS chips are given. The GUM design style is scaleable and suitable for future system-on-chip applications both on and among chips.